Asupan Buah dan Sayur, Asupan Lemak, Aktivitas Fisik Berhubungan dengan Rasio Ldl/Hdl Orang Dewasa - Ahmad Cipta Pratama; Debby Endayani Safitri (ARGIPA (Arsip Gizi dan Pangan), 2019)
Coronary heart disease (cardiovascular) is caused by an abnormal LDL/HDL ratio. LDL and HDL are components of cholesterol which are essential for each cell. The purpose of this research was to know the relationship fat intake, fruit and vegetable intake, and physical activity with LDL/HDL ratio. This study used a cross-sectional method and subjects were selected through accidental sampling with 86 subjects. The results of the chi-square statistic test showed that there were relationships between fruit and vegetable intake, fat intake, and physical activity with LDL/HDL ratio. Keywords: Coronary Heart Disease, Fat Intake, Fruit and Vegetable Intake, LDL/HDL Ratio, Physical Activity